Resolution of otitis media in a humanized mouse model - Son, Ye Lin; Pak, Kwang; Muradagha, Nada; Heo, Kyung Wook; Leichtle, Anke; Kurabi, Arwa (Frontiers in Genetics, 2022)
Otitis media (OM) is one of the largest public health problems of children, and has devastating impacts in developing countries. The substantial medical and human costs involved have led to research to understand the disease and improve treatment. Animal models of OM have yielded critical information about the immune, inflammatory and genetic mechanisms of OM. However, it is important to link animal studies to human immune and inflammatory responses. In recent years, “humanized” mice have become a valuable tool to study the human immune system in an animal model. Here we describe the first use of humanized mice to study OM. We demonstrate that humanized mice with a sufficient degree of engraftment recapitulate a normal middle ear (ME) inflammatory response to bacterial infection, including the recruitment of human immune cells, and exhibit normal recovery. Moreover, these animals exhibit regulated expression of human-specific immune and inflammatory genes in the ME. In contrast, mice with insufficient engraftment fail to resolve OM. This model has a number of potential uses in OM research, including using hematopoetic stem cells from patients with differing degrees of OM susceptibility, to understand the role of human immune responses in proneness to this common childhood disease.